1907
DOI: 10.1113/jphysiol.1907.sp001215
|View full text |Cite
|
Sign up to set email alerts
|

The action of caffeine on the capacity for muscular work

Abstract: THE research of which an account is to be given in this article differs in several respects from previouis attempts to determine the influence of caffeine on the capacity for muscular work in man. The method which has been usually employed has been to take a continuous series of ergograms at intervals of two to five minutes and to administer the caffeine either before or at some stage in this continuous series. Such a method gives no adequate means for the determination of any differential action of the drug i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
5

Year Published

1912
1912
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
1
33
0
5
Order By: Relevance
“…T he ergogenic properties of caffeine have been identified since the early 1900s (29). Early data (8,20) revealed an ergogenic effect of caffeine on endurance performance.…”
Section: Introductionmentioning
confidence: 99%
“…T he ergogenic properties of caffeine have been identified since the early 1900s (29). Early data (8,20) revealed an ergogenic effect of caffeine on endurance performance.…”
Section: Introductionmentioning
confidence: 99%
“…Simple beliefs and expectations can trigger spontaneous self-healing in patients. Indeed, this effect is so strong that clinical trials should be conducted as double-blind experiments (Rivers and Webber 1907). It does not suffice to keep the patients ignorant about which pill is the actual medicine and which one is simply a sugar tablet.…”
Section: The Mind-body Problemmentioning
confidence: 99%
“…For more than one hundred years, caffeine has been known to have an ergogenic effect on muscular work. 1 In particular, the efficacy of caffeine has been well-documented in dynamic exercise in which aerobic metabolism predominates. 2 A recent study showed that 74% of competitive athletes use caffeine due to its ergogenic capabilities.…”
Section: Introductionmentioning
confidence: 99%